2018
DOI: 10.1063/1.5022049
|View full text |Cite
|
Sign up to set email alerts
|

CMOS compatible W/CoFeB/MgO spin Hall nano-oscillators with wide frequency tunability

Abstract: We demonstrate low-operational-current W/Co 20 Fe 60 B 20 /MgO spin Hall nanooscillators (SHNOs) on highly resistive silicon (HiR-Si) substrates. Thanks to a record high spin Hall angle of the β-phase W (θ SH = -0.53), a very low threshold current density of 3.3 × 10 7 A/cm 2 can be achieved. Together with their very wide frequency tunability (7-28 GHz), promoted by a moderate perpendicular magnetic anisotropy, this makes HiR-Si/W/CoFeB based SHNOs potential candidates for wide-band microwave signal generation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 32 publications
0
55
1
Order By: Relevance
“…14 For most of these applications, the SHNO performance needs to be enhanced to offer low threshold currents (low power consumption), high microwave output power, and low linewidth. While it has been shown that the synchronization of two or more SHNOs can be used to improve the power and coherency of the generated microwave signal, [15][16][17] several studies have also focused on enhancing the efficiency of spin current generation by using other heavy metals with higher n SH , such as b-W, [18][19][20] b-Ta, 21 and V. 22 Compared to Pt, these materials typically suffer from excessive heating due to their higher resistivity, which can be problematic when a large number of them are placed together in a small area to operate collectively, increasing the proportion of the current going through the ferromagnetic layer.…”
mentioning
confidence: 99%
“…14 For most of these applications, the SHNO performance needs to be enhanced to offer low threshold currents (low power consumption), high microwave output power, and low linewidth. While it has been shown that the synchronization of two or more SHNOs can be used to improve the power and coherency of the generated microwave signal, [15][16][17] several studies have also focused on enhancing the efficiency of spin current generation by using other heavy metals with higher n SH , such as b-W, [18][19][20] b-Ta, 21 and V. 22 Compared to Pt, these materials typically suffer from excessive heating due to their higher resistivity, which can be problematic when a large number of them are placed together in a small area to operate collectively, increasing the proportion of the current going through the ferromagnetic layer.…”
mentioning
confidence: 99%
“…In certain materials (e.g. Pt [13], Ta [27] and W [28], [29]), the conversion ratio from charge to spin current, called spin-Hall angle (SHA) is large enough to exert a sufficient torque on an adjacent FL to excite magnetization precession. The three-terminal MTJ-SHNO architecture proposed in [16] is based on these principles where a Ta strip is providing spin injection into the FL.…”
Section: A Basic Operation Of Three-terminal Mtj-shnos With Vcmamentioning
confidence: 99%
“…In AMR, the resistance of the material is at a maximum when the current and magnetization are in a parallel configuration, and at a minimum when perpendicular. For a typical thin ferromagnetic layer, the AMR value is less than 1% at room temperature [55]; however, in emerging semimetal topological materials, it can reach a few hundred percent [56]. The resistivity can then be described through the angular dependency:…”
Section: Theoretical Background 1anisotropic Magnetoresistancementioning
confidence: 99%